PEMANFAATAN MEDIA SOSIAL DALAM RANGKA PENINGKATAN PELAYANAN PUBLIK - Muh. Ryan Rahmatul Hidayat; Imanuel Rivaldo Wenggi (Institut Pemerintahan Dalam Negeri (IPDN), 2022)
The DKI Jakarta Provincial Government responds to the impact of globalization with the urgency of digitizing communication media between the government and its people. The response aims to establish a two-way relationship between the government and the community. The purpose of this study was to determine the use of social media to improve public services in a study on the @DKIjakarta twitter account. This study uses a qualitative descriptive approach by analyzing qualitative data in the form of documents, the appearance of the twitter account application and the results of the research which are described through descriptions in the narrative. The results of this study found that there were several efforts made by the DKI Jakarta provincial government to improve the quality of public services through the @DKIJakarta twitter account through easy access to the @DKIJakarta twitter account, increasing the content on the @DKIJakarta twitter account, and updating the display of data & information. Improving the quality of public services provided can improve the image of the DKI Jakarta Provincial government in the eyes of the community. The digitization of communication media shown by DKI Jakarta shows its existence as a region that upholds the principle of transparency in good governance through the use of twitter accounts